A User Information Needs Study of the McMaster University Library Web Site - Wagner, Nicole; Detlor, Brian (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper discusses an information needs study of the McMaster University Library web site in an effort to improve the design and utility of the site from various user perspectives. Study findings and recommendations for future web site development are discussed, many generalizable to academic library web sites at large. Cette communication présente une étude sur les besoins informationnels des utilisateurs sur le site Web de la bibliothèque de l’Université McMaster afin d’améliorer la conception et l’utilité du site Web selon le point de vue de différents utilisateurs. On y discute des résultats de l’étude et des recommandations pour la conception de futurs sites Web, dont plusieurs peuvent être généralisés à l’ensemble des sites Web de bibliothèques universitaires.